Long Distance Electron-Transfer Mechanism in Peptidylglycine α-Hydroxylating Monooxygenase: A Perfect Fitting for a Water Bridge - de la Lande, Aurélien; Martí, Sergio; Parisel, Olivier; Moliner, Vicent (Journal of the American Chemical Society, 2007)
The active sites of copper enzymes have been the subject of many theoretical and experimental investigations from a number of years. Such studies have embraced topics devoted to the modeling of the first coordination sphere at the metallic cations up to the development of biomimetic, or bioinspired, catalytic systems. At least from the theoretical viewpoint, fewer efforts have been dedicated to elucidate how the two copper cations act concertedly in noncoupled dicopper enzymes such as peptidylglycine α-hydroxylating monooxygenase (PHM) and dopamine β-monooxygenase (DβM). In these metalloenzymes, an electronic transfer is assumed between the two distant copper cations (11 Å). Recent experimental results suggest that this transfer occurs through water molecules, a phenomenon which has been theoretically evidenced to be of high efficiency in the case of cytochrome b 5 (Science, 2005, 310, 1311). In the present contribution dedicated to PHM, we overpass the common theoretical approaches dedicated to the electronic and geometrical structures of sites CuM or CuH restricted to their first coordination spheres and aim at directly comparing theoretical results to the experimentally measured activity of the PHM enzyme. To achieve this goal, molecular dynamics simulations were performed on wild-type and various mutants of PHM. More precisely, we provide an estimate of the electron-transfer efficiency between the CuM and CuH sites by means of such molecular dynamics simulations coupled to Marcus theory joined to the Beratan model to approximate the required coupling matrix elements. The theoretical results are compared to the kinetics measurements performed on wild and mutated PHM. The present work, the dynamic aspects of which are essential, accounts for the experimental results issued from mutagenesis. It supports the conclusion that an electronic transfer can occur between two copper(I) sites along a bridge involving a set of hydrogen and chemical bonds. Residue Gln170 is evidenced to be the keystone of this water-mediated pathway.